2012
DOI: 10.1074/jbc.m112.383273
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent MicroRNA-125b Up-regulation Promotes Cell Survival by Targeting p38α upon Ultraviolet Radiation

Abstract: Background: UV radiation-induced miRNA expression modulates cellular stress response. Results: UV up-regulates miR-125b expression via ATM-dependent NF-B activation, which represses p38␣ expression. Conclusion: UV-induced miR-125b prevents prolonged p38␣ activation and thereby promotes cell survival. Significance: Up-regulation of miR-125b serves as a negative feedback mechanism to control p38␣ activity upon UV radiation, which may contribute to tumorigenesis of skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 53 publications
5
59
0
1
Order By: Relevance
“…18,[20][21][22][23][24][25][26][27][28] Here we examine the expression of genes listed in Supplementary Table 3 for their response to transfection of control miRNA, miR-125B antagomiR, miR-29B mimic and miR-125B antagomiR in combination with miR-29B mimic. Figure 6a shows that MYBL2, AKT2, CDK4 and SP1 are inhibited by miR-29B mimic in THP-1 cells; we also observe that AKT2 and CDK4 are further inhibited by the addition of miR-125B antagomiR.…”
Section: Mir-29b and Mir-125b Gene Targets In Human Amlmentioning
confidence: 99%
“…18,[20][21][22][23][24][25][26][27][28] Here we examine the expression of genes listed in Supplementary Table 3 for their response to transfection of control miRNA, miR-125B antagomiR, miR-29B mimic and miR-125B antagomiR in combination with miR-29B mimic. Figure 6a shows that MYBL2, AKT2, CDK4 and SP1 are inhibited by miR-29B mimic in THP-1 cells; we also observe that AKT2 and CDK4 are further inhibited by the addition of miR-125B antagomiR.…”
Section: Mir-29b and Mir-125b Gene Targets In Human Amlmentioning
confidence: 99%
“…RNA Extraction, Reverse Transcription, and Quantitative Real-time PCR-Total RNA was extracted with TRIzol (Invitrogen) and retrotranscribed with a first-strand cDNA synthesis kit (Thermo Scientific). Real-time PCR analyses were performed in triplicate as described previously (33). The housekeeping gene GAPDH was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Although, these miRNAs can regulate not only NF-κB bio-molecular mechanism but also involve in various type of signaling pathways in neoplasia (Davis & Hata, 2009). On the other (Kim et al, 2012;Tan et al, 2012;Xia et al, 2014).…”
Section: A Bridging Avenue To Ameliorate Oncogenesis Through Mirnas Amentioning
confidence: 99%
“…It is also essential to counter this PCD in cancer cells via dephosphorylation of BCl-2. Next, Tan et al (2012) showed, activation of NF-κB by UV is required for miR-125b induction in colon cancer and OS.…”
Section: A Bridging Avenue To Ameliorate Oncogenesis Through Mirnas Amentioning
confidence: 99%
See 1 more Smart Citation